Natural Product Alantolactone Targeting AKR1C1 Suppresses Cell Proliferation and Metastasis in Non-Small-Cell Lung Cancer - Fu, Zhiwen; Li, Shijun; Liu, Jinmei; Zhang, Cong; Jian, Chen; Wang, Lulu; Zhang, Yu; Shi, Chen (Frontiers in Pharmacology, 2022)
Non-small-cell lung cancer (NSCLC) is one of the leading causes of cancer-related deaths, characterized by high invasion and metastasis. Aldo-keto reductase family 1 member C1 (AKR1C1) plays an important role in cancer cell proliferation and metastasis, and has gained attention as an anticancer drug target. Here, we report that the natural sesquiterpene lactone alantolactone (ALA) was shown to bind directly to AKR1C1 through the Proteome Integral Solubility Alteration (PISA) analysis, a label-free target identification approach based on thermal proteome profiling. Acting as a specific inhibitor of AKR1C1, ALA selectively inhibits the activity of AKR1C1 and ALA treatment in human non-small-cell lung cancer (NSCLC) cell results in a reduction in cell proliferation and metastasis, inhibition of AKR1C1 expression, and deactivation of STAT3. Moreover, ALA inhibited tumor growth in vivo, and the inhibition of AKR1C1 and STAT3 activation were also found in the murine xenograft model. Collectively, our work not only gives mechanistic insights to explain the bioactivity of ALA in anticancer but also provides opportunities of developing novel sesquiterpene lactone-based AKR1C1 inhibitors for the treatment of NSCLC.